ABOUT THE LEGAL DEFINITION OF WASTE - Šogorov, Stevan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The paper is based on the statement that the adequate legal definition of waste is one of the key prerequisites of successful implementation of regulations on environmental protection. By analysing EU, German and Serbian regulations, the author comes to the conclusion that for the concept of waste several elements of the objective and subjective character are necessary. It is necessary to objectively determine waste as chattel. However, in order for a thing to become waste, it is necessary for its possessor (who may not necessarily be the owner) to disclaim it, want to disclaim it or be required to disclaim it. Therefore, in the conclusion of the analysis waste is legally defined as any chattel its possessor disclaims, wants to disclaim or is required to disclaim.